Anti-Corruption Education Model Based on Local Wisdom in Social Studies Learning at Junior High School in the City of Semarang - Noviani Achmad Putri; Eko Handoyo; Martitah Martitah; Moh. Solehatul Mustofa (Universitas Negeri Semarang, 2023)
Indonesia is one of the countries with a high level of corruption. Corruption in Indonesia is already seen as an extraordinary crime. Corruption has become a frightening scourge and destroys the life of the nation. Corruption behavior is closely related to consumerism and hedonism. But on the other hand, as a plural nation, Indonesia has so much local wisdom that can ward off corrupt behavior. This can happen because local wisdom in Indonesia includes shame, simple life, and socialism. As a tribe that has a distinctive culture of shame, local wisdom in the community has a very important role in shaping the character of the younger generation to have an anti-corruption character. One of the efforts to eradicate corruption with preventive measures is through the implementation of anti-corruption education in social science learning. This study examines the contribution of local wisdom in efforts to prevent corrupt behavior in Indonesia. This research was conducted in junior high schools 3, 9, and 32 in Semarang City, using qualitative methods. Data collection techniques use observation, interviews, and documentation. Test the validity of data using triangulation techniques and source triangulation and analyzed the stages of data collection, data reduction, data presentation, and conclusions. The result of this research is that the anti-corruption education model can be carried out through several strategies, namely by strengthening reading literacy, optimizing digital literacy, and cultural literacy. First, by increasing reading literacy, students can read from various literature, both from reference books, textbooks, modules, diktats, research journals, and e-books related to Anti-Corruption Education; Secondly, by optimizing digital literacy, students can improve their digital literacy through various anti-corruption educational game applications, e-books, e-modules, and various social media such as Tiktok, Instagram, Twitter, Facebook; Third, strengthening cultural literacy, students can learn about local wisdom that contains anti-corruption character values through Javanese culture that they have learned.